Dry matter production and nutritive value of alfalfa (Medicago sativa L.) and orchradgrass (Dactylis glomerata L.) under different light regimes - Costa Varella, Alexandre (2001)
Spring and summer alfalfa dry matter and nitrogen production rates were greater than orchardgrass in open pasture and under three shade levels. Ten year old Pinus radiata allowed 60% light transmissivity. The addition of artificial shade resulted in 45% and 25% transmissivity. Orchardgrass pastures were nitrogen deficient and water stressed. In contrast, alfalfa was not stressed and it was more light responsive than orchardgrass. Differences in nutritive value were relatively small between species and between light regimes. Sheep liveweight gain on alfalfa was greater than on orchardgrass. Orchardgrass demonstrated shade tolerance, but alfalfa was more productive even at 25% transmissivity. Conventional concepts of shade tolerance may not be appropriate when screening pasture species for silvopastoral systems.